Pricing by international airline alliances: a retrospective study using supplementary foreign-carrier fare data - Jan K. Brueckner; Ethan Singer (Center for Economic Studies and ifo Institute (CESifo), 2019)
This study provides further empirical evidence on pricing by international airline alliances. The paper covers a long sample period, which runs from 1997 to 2016, and it supplements the usual USDOT fare data with confidential fare data reported by the foreign alliance partners of US carriers. The empirical results for connecting service match earlier findings, with alliances charging lower fares than nonaligned carriers. The GTG results imply that, in the latter part of the sample period, granting antitrust immunity to two previously nonaligned carriers is equivalent to removing a competitor, with a consequent increase in fares (an effect seldom seen in previous work).
Keywords: 330